Routing and Spectrum Allocation in Elastic Optical Networks: A Tutorial - V. Varalakshmi, S. Leelashyam, M Venkataratnam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
We describe an iterative site-based method for estimating the impulse response of optical wireless channels. The method allows for the simultaneous evaluation of channels for many receiver or transmitter locations, thus providing significantly improved calculation times. A simple geometrical model of indoor environments is presented which includes interior features such as partitions, people, and furniture, thus permitting accurate evaluation of shadowing effects. We demonstrate that by considering multiple receiver or transmitter locations, we can improve calculation times by a factor of more than a thousand. The tool is applied to the problem of developing propagation models for randomly oriented transmit- ters and receivers inside rooms. Our study shows channel gain variations at a fixed transmitter/receiver separation of more than 20 dB. At large separations, receivers with LOS paths to the transmitters receive on average 7 dB more power than those with no LOS. We also show average RMS delay spreads increasing with distance and ranging from 4 ns to 7 ns for non-LOS channels and up to 3 ns for LOS channels. Finally, in furnished rooms we show that accurate estimation of channel parameters requires calculation of at least four-bounce impulse responses.